An on-line measurement method of injection rate of high pressure common rail system. (January 2021) - Dong, Quan; Yang, Xiyu; Ni, Hao; Song, Jingdong; Lu, Changhao; Ni, Zuo
Highlights: An innovative on-line measurement method of engine fuel injection rate is proposed. Riemann wave theory is applied to propose the decoupling method of superposed pressure wave. A method of judging the key moment of the fuel injection process is proposed. The method can achieve quite good precision in experiment. Abstract: This paper presents a new on-line measurement method of injection rate based on the injector inlet pressure. The Riemann wave theory is applied to the fuel system, and the mathematical relationship of injection rate (G) and pressure (P) under single Riemann wave is put forward. The correction algorithm of the interference wave and the decoupling method of the superposition wave are proposed, which improves the accuracy of the algorithm and realizes the calculation of the fuel injection rate during the long injection energizing time. The identification algorithm of the needle maximum upstroke position moment and the needle starting downstroke moment are proposed and taken as the key time characteristics of the injection process. Compared to the experiments, the errors of the injection mass by this method were within 3%, and the fitting goodness of injection rate curve exceeded 0.93, proving quite good precision for the method.